PROTECTION LAW RIGHT CREATION SONG IN COMMERCIAL PERFORMANCE BY A DISC JOCKEY - Dinar Aryo Seno; Sunarjo (Faculty of Law, Widya Gama University, Malang, 2026)
Song copyright is the legal protection of musical works that include lyrics, melodies, and arrangements produced by the creator. In the context of Indonesian law, copyright gives exclusive rights to the creator or right holder to regulate the use, distribution, and reproduction of his work. There are two exclusive rights that arise, namely moral rights and economic rights. Moral rights that include the right to distribute, reproduce, disseminate, and bring for commercial purposes. While Economic Rights are the right to obtain economic interests such as royalties. This writing aims to find out other regulations relating to legal protection for copyright holders when the song is remixed by disk jockeys and used for commercial purposes such as performances. In addition, this paper also aims to understand the legal remedies that can be done in the event of copyright infringement by disk jockey. The research method used in this research is a Normative Approach, with a Statue Approach problem approach method, with library data collection techniques and using data analysis methods is Qualitative which analyzes legal language based on data. The results of the study show that legal protection of owners or copyright holders whose songs are used by disk Jockeys in commercial performances have been regulated in Law 28 of 2014 and regarding royalty payments contained in Government Regulation No. 56 of 2021, but has not specifically regulated the song remixed by disk jockeys. Moreover, disk jockeys should pay royalties because it's commercial use of songs has been regulated in Article 9 Paragraph 3 and Article 23 Paragraph 5 of Law Number 28 of 2014 concerning Copyright.